Numerical modelling of the Concrete Beams Strengthened with externally bonded CFRP Fabrics at High Temperatures - mahmood naderi (Iranian Society of Structrual Engineering (ISSE), 2019)
The use of externally bonded fiber reinforced polymer (FRP) has been proven to be an effective and efficient method to strengthen deficient concrete components and structures. This paper presents numerical investigations on the de-bonding behavior of concrete beams strengthened with externally bonded CFRP fabrics, at elevated temperatures. The numerical study was carried out, using the commercial package, “Abaqus”, for finite element analysis. The simulation was validated against laboratory four point bending tests of nine plain concrete beams previously performed by the authors. The behavior of concrete beams with three different design concrete strength of 20, 30 and 40 MPa which were externally bonded by CFRP fabrics were investigated at -20, +20, +50 and +80 Degree Celsius. Linear elastic isotropic and orthotropic models were used for the CFRP layer and a cohesive bond model was used for the concrete – CFRP interface. A plastic damage model was also used for the concrete. In the finite element analysis, similar to the laboratory tests, the specimens were first heated up to the elevated temperatures, and then loaded up to failure. The results show good agreement with the experimental data, regarding the failure loads, load–displacement response, and crack patterns. The finite element results of thermal strains in CFRP and stresses in the concrete are also compared with the thermal strains and stresses, determined by the analytically models.